QTL and Transcriptomic Analyses Implicate Cuticle Transcription Factor SHINE as a Source of Natural Variation for Epidermal Traits in Cucumber Fruit - Rett-Cadman, Stephanie; Colle, Marivi; Mansfeld, Ben; Barry, Cornelius S.; Wang, Yuhui; Weng, Yiqun; Gao, Lei; Fei, Zhangjun; Grumet, Rebecca (Frontiers in Plant Science, 2019)
The fruit surface is a unique tissue with multiple roles influencing fruit development, post-harvest storage and quality, and consumer acceptability. Serving as the first line of protection against herbivores, pathogens, and abiotic stress, the surface can vary markedly among species, cultivars within species, and developmental stage. In this study we explore developmental changes and natural variation of cucumber (Cucumis sativus L.) fruit surface properties using two cucumber lines which vary greatly for these traits and for which draft genomes and a single nucleotide polymorphism (SNP) array are available: Chinese fresh market type, Chinese Long ‘9930’ (CL9930), and pickling type, ‘Gy14’. Thin-section samples were prepared from the mid-region of fruit harvested at 0, 4, 8, 12, 16, 20, 24 and 30 days post pollination (dpp), stained with Sudan IV and evaluated for cuticle thickness, depth of wax intercalation between epidermal cells, epidermal cell size and shape, and number and size of lipid droplets. ‘Gy14’ is characterized by columnar shaped epidermal cells, a 2-3 fold thicker cuticular layer than CL9930, increased cuticular intercalations between cells and a larger number and larger sized lipid droplets. In both lines maximal deposition of cuticle and increase in epidermal size coincided with exponential fruit growth and was largely completed by approximately 16 dpp. Phenotyping and quantitative trait locus mapping (QTL) of fruit sampled from an F7:F8 Gy14 × CL9930 recombinant inbred line (RIL) population identified QTL regions on chromosomes 1, 4 and 5. Strong QTL for epidermal cell height, cuticle thickness, intercalation depth, and diameter of lipid droplets co-localized on chromosome 1. SSR markers on chromosome 1 were used to screen for recombinants in an extended RIL population to refine the QTL region. Further fine mapping by KASP assay combined with gene expression profiling suggested a small number of candidate genes. Tissue specificity, developmental analysis of expression, allelic diversity and gene function implicate the regulatory factor CsSHINE1/WIN1 as a source of natural variation for cucumber fruit epidermal traits.